Combination of SDS‐PAGE and intact mass analysis for rapid determination of heterogeneities in monoclonal antibody therapeutics. Issue 9 (22nd March 2017) - Yamada, Hideaki; Matsumura, Chiemi; Yamada, Keita; Teshima, Koichiro; Hiroshima, Takashi; Kinoshita, Mitsuhiro; Suzuki, Shigeo; Kakehi, Kazuaki
Abstract : mAbs are currently mainstream in biopharmaceuticals, and their market has been growing due to their high target specificity. Characterization of heterogeneities in mAbs is performed to secure their quality and safety by physicochemical analyses. However, they require time‐consuming task, which often strain the resources of drug development in pharmaceuticals. Rapid and direct method to determine the heterogeneities should be a powerful tool for pharmaceutical analysis. Considering the advantages of electrophoresis and MS, this study addresses the combination of SDS‐PAGE and intact mass analysis, which provides direct, rapid, and orthogonal determination of heterogeneities in mAb therapeutics. mAb therapeutics that migrated in SDS‐PAGE were recovered from gel by treatment with SDC‐containing buffer. Usage of SDC‐containing buffer as extraction solvent and ethanol‐based staining solution enhanced the recovery of intact IgG from SDS‐PAGE gels. Recovery of mAbs reached more than 86% with 0.2% SD. The heterogeneities, especially N ‐glycan variants in the recovered mAb therapeutics, were clearly determined by intact mass analysis. We believe that the study is important in pharmaceuticals‧ perspective since orthogonal combination of gel electrophoresis and intact mass analysis should be pivotal role for rapid and precise characterization of mAbs.